2021
DOI: 10.1097/sap.0000000000002808
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Enhanced Recovery Pathways in Craniosynostosis

Abstract: Background Enhanced Recovery After Surgery (ERAS) pathways are multimodal approaches aimed at minimizing postoperative surgical stress, reducing hospitalization time, and lowering hospitalization charges. Enhanced Recovery After Surgery is broadly and increasingly implemented in hospitals across the country. Early reports have shown ERAS to reduce length of stay (LOS) after commonly performed pediatric surgeries. However, LOS and hospital charges after craniosynostosis have not been studied. We hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…While ERAS pathways implemented in other neurosurgical and craniofacial procedures have been shown to reduce hospital LOS, 27,28 national trends suggest that the implementation of ERAS protocols following cranial vault surgery has not replicated the same success. In a retrospective review of 22,916 patients undergoing cranial vault surgery for craniosynostosis between 2007 and 2014 queried from the Healthcare Cost and Utilization Project's National Inpatient Sample, Wu et al 17 failed to observe a decrease in LOS despite an increase in the adoption of ERAS protocols during the same period. Other studies have advocated for admitting postoperative patients to the wards rather than the ICU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While ERAS pathways implemented in other neurosurgical and craniofacial procedures have been shown to reduce hospital LOS, 27,28 national trends suggest that the implementation of ERAS protocols following cranial vault surgery has not replicated the same success. In a retrospective review of 22,916 patients undergoing cranial vault surgery for craniosynostosis between 2007 and 2014 queried from the Healthcare Cost and Utilization Project's National Inpatient Sample, Wu et al 17 failed to observe a decrease in LOS despite an increase in the adoption of ERAS protocols during the same period. Other studies have advocated for admitting postoperative patients to the wards rather than the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,[11][12][13][14] Therefore, a better understanding of patient risk factors portending to inferior outcomes after CVR are necessary to improve patient care and reduce health care resource utilization. [15][16][17] In recent studies, length of stay (LOS) has arisen as a proxy for health care expenditure and quality of care. 18,19 In a retrospective review of 3246 patients identified through the Kids' Inpatient Database (KID) undergoing surgical reconstruction for craniosynostosis, Nguyen et al 20 found that prolonged LOS was associated with a significant increase in health care costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In neurosurgery specifically, extended LOS and unplanned readmissions have been associated with greater rates of complications, mortality, and health care costs 7–9 . Analogous findings apply to cases of cranial vault remodeling (CVR) for craniosynostosis, the premature closure of at least one cranial suture 10–12 . Craniosynostosis impacts ∼1:715 to 1:2500 live births and accrues an estimated $66,606 for each CVR procedure, motivating the identification of risk factors that may engender inferior surgical outcomes after CVR 13 …”
mentioning
confidence: 99%
“…[7][8][9] Analogous findings apply to cases of cranial vault remodeling (CVR) for craniosynostosis, the premature closure of at least one cranial suture. [10][11][12] Craniosynostosis impacts ∼1:715 to 1:2500 live births and accrues an estimated $66,606 for each CVR procedure, motivating the identification of risk factors that may engender inferior surgical outcomes after CVR. 13 One modifiable risk factor, extended operative time (EOT), has been linked to postoperative complications, extended LOS, and unplanned readmissions.…”
mentioning
confidence: 99%